2015
DOI: 10.1371/journal.pone.0125239
|View full text |Cite
|
Sign up to set email alerts
|

Warming and Ocean Acidification Effects on Phytoplankton—From Species Shifts to Size Shifts within Species in a Mesocosm Experiment

Abstract: While the isolated responses of marine phytoplankton to climate warming and to ocean acidification have been studied intensively, studies on the combined effect of both aspects of Global Change are still scarce. Therefore, we performed a mesocosm experiment with a factorial combination of temperature (9 and 15°C) and pCO2 (means: 439 ppm and 1040 ppm) with a natural autumn plankton community from the western Baltic Sea. Temporal trajectories of total biomass and of the biomass of the most important higher taxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
88
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 46 publications
7
88
0
1
Order By: Relevance
“…Rhizosolenia spp. were seen to cope well with more acidic conditions, which reflects some previous studies (Sommer et al, 2015). In contrast, Corethron spp.…”
Section: Phytoplankton Communitysupporting
confidence: 86%
“…Rhizosolenia spp. were seen to cope well with more acidic conditions, which reflects some previous studies (Sommer et al, 2015). In contrast, Corethron spp.…”
Section: Phytoplankton Communitysupporting
confidence: 86%
“…Moreover, summer ocean surface temperatures at the location 301 of isolation usually reach 6°C or more (Hegseth et al, in press). Our results are also in line with 302 mesocosm experiments that indicate stimulatory effects of warming on picoplankton 303 abundances (Daufresne et al, 2009;Sommer et al, 2015) as well as with the temperature 304 optimum of 6-8°C observed for another Arctic strain of M. pusilla (Lovejoy et al, 2007). 305…”
Section: Micromonas Pusilla Benefits From Warming 296supporting
confidence: 80%
“…Tolerance of CO 2 levels up to ∼ 1000 µatm has often been observed in natural phytoplankton communities in regions exposed to fluctuating CO 2 levels. In these communities, increasing CO 2 often had no effect on primary productivity (Tortell et al, 2000;Tortell and Morel, 2002;Tortell et al, 2008b;Hopkinson et al, 2010;Tanaka et al, 2013;Sommer et al, 2015;Young et al, 2015;Spilling et al, 2016) or growth (Tortell et al, 2008b;Schulz et al, 2013), although an increase in primary production has been observed in some instances (Riebesell, 2004;Tortell et al, 2008b;Egge et al, 2009;Tortell et al, 2010;Hoppe et al, 2013;Holding et al, 2015). These differing responses may be due to differences in community composition, nutrient supply, or ecological adaptations of the phytoplankton community in the region studied.…”
Section: Ocean Acidification Effects On Phytoplankton Productivitymentioning
confidence: 89%